Assessment of Power Quality Improvement in a Micro WECS with Battery Storage under Critical Load Condition - M. Vimalraj; R. Umamageswari (New Visions in Science and Technology Vol. 11, 2021)
In the micro-grid system, it is particularly complicated to maintain the critical load with continuous power supply. The proposed micro-wind energy conversion system with battery energy storage is used to exchange the controllable real and reactive power in the grid and to sustain the power quality norms at the point of common coupling. The generated micro wind power can be stored in the batteries at low power demand hours. The combination of battery energy storage and micro-wind generating system in distributed power system can provide the effective, reliable, and durable power system. In this scheme, inverter control is executed with hysteresis current control mode to achieve the faster dynamic switchover for the support of critical load. The combination of battery storage with micro-wind energy generation system (\(μ\)WEGS), which will synthesize the output waveform by injecting or absorbing reactive power and enable the real power flow required by the load. The system reduces the burden on the conventional source and utilizes \(μ\)WEGS and battery storage power under critical load constraints. The system provides rapid response to support the critical loads. The scheme can also be operated as a stand-alone system in case of grid failure like a uninterrupted power supply. The system is simulated in MATLAB/SIMULINK and results are presented.